THE EFFECT OF TABLETOP DISASTER EXERCISE (TDE) ON EMERGENCY RESPONSE PREPAREDNESS FLOOD DISASTER IN ADOLESCENTS IN THE VILLAGE SIWALAN KEDUNGDALEM DRINGU PROBOLINGGO - Salamah, Ummatus; Achmad Kusyairi; Dodik Hartono (Media Inovasi Pendidikan dan Publikasi, 2023)
TDE simulation is a simulation that is carried out by playing role plays by all participants to solve problems related to the management of disaster victims on a three-dimensional table board media so that knowledge and skills in disaster emergency response can increase through analysis of problem solving contained in previously created scenarios. . The research method used in this research is One Group pre test and post test design. The sampling technique used was proportionate random sampling for all teenagers according to the inclusion and exclusion sample size of 79 respondents. The Wilcoxon test results showed a p value: 0.000<0.05. This shows that there is an influence of the Tabletop Disaster Exercise (TDE) simulation on flood disaster emergency response readiness among teenagers in Siwalan Hamlet, Kedungdalem Village, Dringu District, Probolinggo Regency.